Correction: Bottom-up fabrication of artery-mimicking tubular co-cultures in collagen-based microchannel scaffolds. (2nd September 2016) - Tan, A.; Fujisawa, K.; Yukawa, Y.; Matsunaga, Y. T.
Abstract : Correction for 'Bottom-up fabrication of artery-mimicking tubular co-cultures in collagen-based microchannel scaffolds' by A. Tan, et al., Biomater. Sci., 2016, DOI: 10.1039/c6bm00340k.